2013
DOI: 10.1242/dev.097477
|View full text |Cite
|
Sign up to set email alerts
|

Foxp1 maintains hair follicle stem cell quiescence through regulation of Fgf18

Abstract: SUMMARYHair follicles cyclically degenerate and regenerate throughout adult life and require regular stem cell activation to drive the cycle. In the resting phase of the hair cycle, hair follicle stem cells are maintained in a quiescent state until they receive signals to proliferate. We found that the forkhead transcription factor Foxp1 is crucial for maintaining the quiescence of hair follicle stem cells. Loss of Foxp1 in skin epithelial cells leads to precocious stem cell activation, resulting in drastic sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 40 publications
(62 reference statements)
6
64
0
Order By: Relevance
“…38 FOXP1, like certain other FOX proteins, might thus compete for binding the same DNA motifs of some FOXO target promoters as described in a few contexts. 22,33,39 As opposed to HSPCs, FOXP1 maintains hair follicle stem cell quiescence, 40 whereas it sustains ESC self-renewal and contributes to efficient reprogramming of somatic cells into induced pluripotent stem cells. 41 The reasons behind these paradoxical observations are unclear, but may be linked to expression of dedicated spliced variants of FOXP1 observed in some cellular contexts, [42][43][44][45] as exemplified in ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…38 FOXP1, like certain other FOX proteins, might thus compete for binding the same DNA motifs of some FOXO target promoters as described in a few contexts. 22,33,39 As opposed to HSPCs, FOXP1 maintains hair follicle stem cell quiescence, 40 whereas it sustains ESC self-renewal and contributes to efficient reprogramming of somatic cells into induced pluripotent stem cells. 41 The reasons behind these paradoxical observations are unclear, but may be linked to expression of dedicated spliced variants of FOXP1 observed in some cellular contexts, [42][43][44][45] as exemplified in ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work demonstrating that activation of the keratinocytes abutting the DP is the first step of anagen strengthened the apparent relevance of this hypothesis (Greco et al 2009). Manipulation of signaling pathways in follicular keratinocytes has shown that activation of the Wnt/ b-catenin pathway promotes anagen initiation, whereas both bone morphogenetic protein (BMP) signaling and fibroblast growth factor (FGF)-18 (expressed from the keratinocytes coating the club hair) prolong the telogen phase Van Mater et al 2003;Kobielak et al 2007;Kimura-Ueki et al 2012;Leishman et al 2013). The DPexpresses Wnts, R-spondins, FGFs, and Noggin, all of which can promote follicle growth and contribute to initiating follicular regeneration (Reddy et al 2001;Rendl et al 2005).…”
Section: Initiation Of the Anagen Phasementioning
confidence: 99%
“…Among the four FOXP proteins, FOXP1 and FOXP2 show a particularly high homology to each other throughout their amino acid sequences (Takahashi et al 2009). Foxp1 and Foxp2 are expressed in diverse organs during embryonic development, often in partially overlapping but distinct patterns (Shu et al 2001, Wang et al 2004, Shu et al 2007, Takahashi et al 2009, Leishman et al 2013, Zhao et al 2015). Analyses of mouse mutants have shown that Foxp1 plays critical roles in development of the spinal motor neurons, lymphocytes, and the cardiomyocytes (Wang et al 2004, Hu et al 2006, Dasen et al 2008, Zhang et al 2010).…”
Section: Introductionmentioning
confidence: 99%